Children with Disabilities: The Social Determinants of Health Affecting the Life Trajectories of Children with Special Needs in Northern Ontario - Annibale, Alexandra (The Meducator, 2016)
The geographical and cultural characteristics of Northern Ontario shape a distinct set of social determinants of health for children growing up with special needs. These determinants, which affect certain cultural groups to a more significant degree, impact a family’s ability to access critical health care resources for the healthy development of a child with special needs. This critical review will explore the nature of these social determinants of health, their observed impacts on child development in current research, and opportunities for health policy to fill current gaps in healthcare resources.